Asymmetric effect of FEARS Sentiment on Stock Returns: Short-sale constraints, limits to arbitrage, and behavioural biases. Issue 11 (2nd September 2022) - Goel, Garima; Dash, Saumya Ranjan; Brooks, Robert; Subramaniam, Sowmya
ABSTRACT: This paper examines the implications of short-sale constraints, limits to arbitrage, and behavioral biases on the FEARS sentiment and stock returns asymmetric relationship. Our results indicate a strong negative relationship between FEARS sentiment and stock return. Our findings show that short-sell and arbitrage constraint attenuates the potential impact of sentiment on return behavior. We find that the FEARS sentiment influences behavioral biases and the trading activity of market participants.